Coproparasitological survey on gastrointestinal parasites in green iguanas (Iguana iguana) of Trinidad and Tobago - W. K. Gafoor; L. Tardieu (Brazilian Journal of Biology)
Abstract The Green iguana (Iguana iguana) is a popular wildlife species in the Latin American and Caribbean (LAC) region, that has been recognized as being host to various parasites and diseases. Despite this significance, few studies address the parasite epidemiology of these species in the Caribbean region and particularly in the island of Trinidad and Tobago where the iguana is recognized as a popular ‘wild’ meat animal. This study investigates the presence of gastrointestinal (GI) parasites in both captive and wild Green iguana populations in Trinidad and Tobago. A total of 52 faecal samples were obtained from wild (n=26) and captive (n=26) iguana populations across both islands and then analysed for parasite egg presence. Results indicated no significant difference between the captive status and sex for parasite load and diversity between captive and wild iguanas. Overall, most individuals exhibited two types of parasite eggs in their faeces (Oxyurids and Ascarids), with three distinct parasite egg types identified (Ascarids, Oxyurids and Tapeworms). This study reveals the parasite load and diversity of GI parasites in Trinidad and Tobago iguana populations, offering insights crucial for wildlife disease and conservation management in the region.